Culturally Speaking The Rhetoric of Voice and Identity in a Mediated Culture - Edgar, Amanda Nell (The Ohio State University Press, 2019)
Examines racial and gendered dimensions of voice in American culture, showing how vocal sound helps to shape cultural power dynamics.